Time‐varying effect of sex on prognosis of lung adenocarcinoma surgical patients in China. Issue 11 (3rd May 2021) - Wang, Zezhou; Mo, Miao; Zhou, Changming; Feng, Xiaoshuang; Shen, Jie; Ye, Ting; Zhang, Yang; Hu, Hong; Chen, Haiquan; Zheng, Ying
Abstract: Background: Little is known about the prognostic advantage of sex for pulmonary adenocarcinoma among Chinese patients. In this study, we aimed to investigate the true sex differences in prognosis by adjusting for confounders and to explore whether the differences were time‐varying. Methods: We identified 4438 lung adenocarcinoma patients who underwent surgery at a regional Cancer Center of China from 2008 to 2016, retrospectively. Sex, age group, smoking history, year of diagnosis and pathological stage were collected. Time‐dependent Cox regression models with inverse probability of treatment weighting (IPTW) based on propensity score were used to assess the effect of sex and account for confounders. Landmark analyses were conducted to assess survival before, and after, five years. Results: Of these patients, 1761 (39.7%) were men and 2677 (60.3%) were women. Median follow‐up time was 52.6 months. After IPTW adjustment, women were found to have significantly better survival than men varying with time in both crude and IPTW models (hazard ratio [HR] [t] = 0.453*1.015 t, where t is the length of time from treatment and its unit is month, p < 0.001). Women had significantly better survival than men within 0–5 years after surgery (HR = 0.763, 95% CI: 0.649–0.897, p = 0.001), whereas there was no difference after five years (HR = 1.135, 95% CI: 0.803–1.605, p = 0.472). In subgroup analysis, women in the 61–71+ age group, in the more than 20 year packs group, pathological stage 0–IB group, and 2013–2016 diagnosis period group revealed the same prognostic pattern. Conclusions: Compared with men, women had better survival after surgical resection of lung adenocarcinoma, especially those who were older and nonsmokers or heavy‐smokers and were pathological stage 0–IB in early years, while the advantage for women diminished with time. Abstract : We analyzed the long‐term survival results of lung adenocarcinoma surgical patients from a large single‐center in China. The survival advantage of women lung adenocarcinoma surgical patients over men is time‐varying. Compared with men, women had better survival after surgical resection of lung adenocarcinoma within five years, especially those who were older, heavy‐smokers and pathological stage 0–IB, but with no significant difference in survival after five years or even in some cases the results in women were inferior to men.